GENETIC OVERLAP BETWEEN INFLAMMATORY BOWEL DISEASE AND PARKINSON'S DISEASE IMPLICATES THE ROLE OF ADAPTIVE IMMUNE RESPONSE IN THEIR COMORBIDITY. (22nd January 2022) - Otten, Thomas; Ayash, Jonathan; Lee, Wonjun; Cheng, Haoxiang; Debebe, Anketse; Hao, Ke; Peters, Lauren; Björkegren, Johan; Kalash, Olivia; Picker, Mellissa; Rendon, Alexa; Colombel, Jean-Frederic; et al.
Abstract: BACKGROUND AND AIMS: Patients with inflammatory bowel disease (IBD), Crohn's disease (CD), and ulcerative colitis (UC) have been shown to be at up to a 40% increased risk of developing Parkinson's disease (PD), a progressive neurodegenerative disorder. Even though a genetic link between IBD and PD was established through shared causal mutations in the LRRK2 gene, it cannot fully explain the observed comorbidity. The goal of this study was to further explore the genetic overlap between these two diseases. METHODS: The polygenic risk scores (PRS), representing estimated genetic determinants for IBD, CD, UC, and PD from previously reported respective genome-wide association studies, were computed using a linear combination of the estimated effects across multiple disease-associated variants in the Parkinson's Progression Markers Initiative (PPMI, www.ppmi-info.org/data ) cohort consisting of 413 PD cases and 195 healthy controls (HC) of predominantly European ancestry. We applied a generalized linear regression model to determine the relationship between IBD-related PRS and PD status while adjusting for sex, age, ethnicity, and principal components (PC1-5). A gene-set enrichment analysis was then conducted using Enrichr to examine the biological pathways associated with the genes regulated by variants intersecting between PRS-IBD and PRS-PD in various tissues relevant to IBD and PD (whole blood, visceral adipose fat, brain, and skeletal muscles). RESULTS: As expected, PRS-PD was significantly elevated in PD patients (odds ratio (OR) 1.76 [95% confidence interval 1.39-2.26], adjusted p=5.34e-06). We also found that PRS-IBD, PRS-CD, and PRS-UC were significantly positively associated with PD case status (OR 1.37 [1.07-1.76], adjusted p=0.01, OR 1.46 [1.15-1.87], adjusted p=0.002, OR 1.36 [1.05-1.76], adjusted p=0.02, respectively, Figure 1). Gene-set enrichment analysis of the intersecting genes between PRS-IBD and PRS-PD across the 4 different relevant tissue types consistently identified the pathways implicating susceptibility to immune-mediated diseases and infections and immune cell differentiation and processing (Figure 2). CONCLUSION: These results further support the genetic link between IBD and PD and emphasize the role of immunity, particularly pertaining to the adaptive immune system in the pathogenesis of both diseases. This is in line with the established role of autoimmunity in IBD etiology and is consistent with recent studies implicating the autoimmune system in PD development. Moreover, our findings suggest that PRS-IBD could serve as an early biomarker of PD and help stratify high-risk IBD patients for future PD prevention interventions.